Effects of Different Concentrations of Eugenol on the Structure and Emulsion Gel Properties of Myofibrillar Protein - Jiaqi LI; Deyin PAN; Jinming MA; Jingjing DIAO; Hongsheng CHEN (Shipin gongye ke-ji)
To explore the effect of eugenol addition on the gel properties of myofibrillar protein emulsions, this study used porcine myofibrillar protein as the research object and simulated the processing of emulsified sausages. The effects of eugenol concentration (0, 5, 10, 20, 50, and 100 mg/g protein) on the protein secondary structure, gel strength, water retention, water distribution, rheology, and microstructure were determined to investigate the effect of eugenol on protein gel formation. The results showed that the addition of low-concentration eugenol (20 mg/g) significantly improved the gel strength and water retention rate of the protein (P<0.05), significantly increased the non-mobile water content and storage modulus of the gel, significantly decreased the cooking loss and freeze-thaw loss (P<0.05), and decreased the free water content of the gel. In contrast, upon the addition of high-concentration eugenol (100 mg/g), the gel strength and water retention were significantly decreased, the cooking loss and freeze-thaw loss were significantly increased, and the gel network structure became rough, and the pore size increased, as revealed by the scanning electron microscopy images. The results confirm that the addition of low-concentration eugenol (20 mg/g) can effectively improve the gel properties of proteins, and it has the potential to be a new type of meat product quality improver.